Distributing Potentiality. Post-capitalist Economies and the Generative Time Regime - Löffler, Davor (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Davor Löffler Title (English): Distributing Potentiality. Post-capitalist Economies and the Generative Time Regime Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 8-44 Page Count: 37 Citation (English): Davor Löffler, “Distributing Potentiality. Post-capitalist Economies and the Generative Time Regime,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 8-44.